Output feedback control for semi-Markovian jump systems with time-varying delay. Issue 3 (2nd July 2020) - Liu, Yuhong; Li, Hui; Zhong, Qishui; Zhong, Shouming
ABSTRACT: This study investigates the problem of output feedback control for semi-Markovian jump systems(S-MJLSs) with time-varying delay. Due to the relaxed conditions on the stochastic process, the S-MJLSs are with time-varying transition rates and can describe a broader class of dynamical systems than the traditional Markovian jump linear systems. Specially, first, by using a novel free-matrix-based integral inequality(FMBII) including well-known integral inequalities as special cases, the H ∞ performance analysis and mode-dependent nonrational synthesis conditions for the underlying S-MJLSs are developed, respectively. Secondly, the conditions obtained in this paper are formulated in terms of linear matrix inequalities (LMIs), which can be efficiently solved via standard numerical software. Finally, numerical examples are presented to demonstrate the effectiveness and advantages of the theoretical results.